Armodafinil and modafinil in the treatment of cancer-related fatigue: A systematic review - Alexa Mcguinness (Annals of Oncology Research and Therapy)
Cancer-related fatigue (CRF) is often cited as the most common and most severe symptom faced by cancer patients, whether that be before they receive a diagnosis of cancer or many years after cessation of cancer therapy or cancer remission. Effective therapy for CRF is lacking, and thus, the development of a treatment to bridge this gap is crucial. Armodafinil and modafinil have displayed off-label uses in the treatment of many conditions characterized by fatigue. Therefore, the aim of this present paper was to evaluate the efficacy of armodafinil and modafinil in alleviating CRF through a review of randomized controlled trials investigating this subject. PubMed was searched to generate pertinent papers for this review, ultimately generating 10 papers after the application of inclusion and exclusion criteria, four and six of which implemented armodafinil-based and modafinil-based interventions, respectively. Armodafinil demonstrated success in alleviating CRF in one study, whereas modafinil improved CRF in three studies. Armodafinil and modafinil may be beneficial for specific subpopulations suffering from CRF, such as cancers associated with higher levels of fatigue or patients with particular pharmacokinetic features, and, as a result, further studies comprising larger and more heterogeneous samples, taking place over longer durations, may allow for more insight into whether armodafinil or modafinil could alleviate CRF.